Problemas emocionais/comportamentais em pré-escolares: associação com indicadores de saúde mental e estilo parental - Silva, Marjorie (2019)
The interaction between children and their caregivers impacts the child development. Research indicates that children of parents who make predominant use of authoritarian and permissive parenting styles have more emotional/behavioral problems than children of those who practice the democratic style. In addition, it is known that parents with mental health problems may have deficits in their educational repertoire and distorted perceptions of their children's behavior. The aim of this study was to analyze associations between emotional/behavioral problems of preschoolers, mothers' mental health indicators and their parenting styles. This is a cross-sectional, quantitative and descriptive study. Seventy-five mothers of children aged 3 to 5 years old who were enrolled in a private/philanthropic elementary school in the state of São Paulo participated in this study. The instruments “Child Behavior Checklist for ages 1½-5” (CBCL/1½-5), “Self-Report Questionnaire” (SRQ-20), “Parenting Styles and Dimensions Questionnaire” (QEDP), and a sociodemographic questionnaire were used. All analyzes were performed using SPSS 21.0 software with significance level of p≤0.05. The results found were: 14.7% to 20% of children with higher than expected emotional/behavioral problems for age and sex, predominant use of permissive parenting style (41.3%) and 16% of mothers with high probability of having a Common Mental Disorder (CMD). Correlations between CBCL/1½-5 scales and Authoritarian Parenting Style were positive with weak indices, while correlations between CBCL/1½-5 and SRQ-20 were positive with moderate to strong indices, which indicates that the more problems the mother perceives in herself, the more problems she observes in her child's behavioral repertoire. Binary logistic regression showed an increase in the child's probability of clinical scores on the emotional/behavioral problem scales in relation to Permissive Parenting Style and mothers with high probability of having a CMD.